The Effect of Gender on Perceptions of Credibility in Child Sexual Assault Cases: A Systematic Review. Issue 2 (17th February 2017) - Voogt, Ashmyra; Klettke, Bianca
ABSTRACT: Child sexual assault cases have one of the highest attrition rates throughout the justice system, with jurors' perceptions of the credibility of the child playing a critical role in the judicial process and resulting outcomes. One of the most prominent influences on credibility is gender, specifically victim and perceiver gender. This article reports the findings of a systematic search of the literature exploring the impact of these factors on perceptions of victim credibility. Results suggest that overall females tend to rate victim credibility higher than do males; however, this gender effect is minimized when the alleged perpetrator is not the biological parent of the victim. There is little support for a victim gender effect, such that potential jurors' ratings of victim credibility does not appear to be influenced by the gender of the victim. The review highlights the lack of consistent and comprehensive measurement of credibility. Legal implications are discussed.